1989
DOI: 10.1139/v89-234
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of Lycopodiumselago. On the identity of selagine with huperzine A and the structure of a related alkaloid

Abstract: Selagine, an alkaloid of Lycopodiumselago, is shown to be identical with huperzine A (2). A minor alkaloid, C15H18N2O2, isolated from L. selago is found to be 6β-hydroxyhuperzine A (4). Keywords: huperzine A, selagine, Lycopodium alkaloids, Alzheimer's disease, acetylcholine esterase inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…In general, besides the basic challenge to analyze the 1D 1 H NMR spectra of extended spin systems of alicyclic compounds, to understand in-depth the 1 H NMR resonances of one typical compound is typically key for the analysis of a whole corresponding structural class. One such example is huperzine A (syn.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, besides the basic challenge to analyze the 1D 1 H NMR spectra of extended spin systems of alicyclic compounds, to understand in-depth the 1 H NMR resonances of one typical compound is typically key for the analysis of a whole corresponding structural class. One such example is huperzine A (syn.…”
Section: Introductionmentioning
confidence: 99%
“…One such example is huperzine A (syn. selagine, 1 isoselagine 2 ), a selagin-type Lycopodium alkaloid, which in the recent past has received considerable attention owing to its interesting acetylcholinesterase (AChE) inhibitory activity 3 -6 and for being a potential drug lead for Alzheimer's disease. 7,8 Huperzine A is currently being tested in 160 patients in a phase II clinical trial sponsored by the NIH (http://clinicaltrials.gov/show/NCT00083590).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huperzine A (1) is isolated from the Chinese folk medicinal plant Huperzia serrata (= Lycopodium serrata) (1) and has been shown to be identical with the alkaloid selagine, which had previously been isolated from L. selago and incorrectly assigned structure 2 (4,5). Huperzine A is reported to increase efficiency for learning and memory in animals (1) and to show promise in the treatment of Alzheimer's disease and myasthenia gravis ( 6 8 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Reinvestigation of these structures has revealed that the earlier structural assignments for selagine and isoselagine are incorrect. In fact, they are identical with HupA [11].…”
Section: Isolation and Structure Elucidationmentioning
confidence: 94%